Evaluation of children's centres in England - strand 3: parenting services in children's centres - Evangelou, M; Goff, J; Hall, J; Sylva, K; Eisenstadt, N; Paget, C; Davis, S; Sammons, P; Smith, T; Tracz, R; Parkin, T (DfE, 2014)
This report forms part of the national evaluation of children’s centres in England (ECCE) research study. The evaluation studies the management, organisation and programmes offered in the centres and a cost-benefit analysis of the programme.